Monoamine signaling and neuroinflammation: mechanistic connections and implications for neuropsychiatric disorders - Saggu, Shalini; Pless, Andrew; Dew, Emily; Ware, Destany; Jiao, Kai; Wang, Qin (Frontiers in Immunology, 2025)
Monoamines, including norepinephrine, serotonin, and dopamine, orchestrate a broad spectrum of neurophysiological and homeostatic events. Recent research shows a pivotal role for monoaminergic signaling in modulating neuroinflammation by regulating proinflammatory cytokines and chemokines within the central nervous system. Importantly, this modulation is not unidirectional; released proinflammatory cytokines markedly “feedback” to influence the metabolism of monoamine neurotransmitters, impacting their synthesis, release, and reuptake. This bidirectional interplay significantly links monoaminergic pathways and neuroinflammatory responses. In this review, we summarize current knowledge of the dynamic interactions between monoamine signaling and neuroinflammation, as well as their critical implications for the pathophysiology of neuropsychiatric disorders, including Parkinson’s Disease, Major Depressive Disorder, and Alzheimer’s Disease. By integrating recent findings, we shed light on potential therapeutic targets within these interconnected pathways, providing insights into novel treatment strategies for these devastating disorders.